Comparative analysis of the influence of different shapes of shaft sections on dust transportation - Liu, Jie; Luo, Xuehua; Wang, Wanqing; Teng, Liangyun; Hao, Chenwei; Cai, Fei; Chen, Yi (Frontiers in Physics, 2024)
Large amounts of dust are generated during digging operations in underground mines, and the transportation of dust is affected by the shape of the roadway section. In order to know the dust transportation law of different cross-section shapes when digging. Fluent software was used to simulate the distribution of wind flow field, dust transportation trajectory, and dust quality concentration in roadways with semicircular arch, three-centered arch, rectangle and trapezium, and then analyze and compare the influence of four cross-section shapes on dust transportation, and use gray correlation analysis to investigate the correlation between the time needed to reduce the dust quality concentration of the roadway to the safe value and the ventilation air volume and air supply distance. The results of the study show that the wind speed in the roadway is in the following order from high to low: rectangle > trapezium > three-centered arch > semicircular arch. Dust particles of each size rubbed each other after blasting, and there were fewer dust particles with larger sizes in the three-centered arch roadway. Both the air supply distance and ventilation air volume impact the dust removal effect; when the air supply distances are 5 m and 10 m, the three-centered arch has a better dust removal effect; when the air supply distances are 15 m and 20 m, the effect is better in the rectangular roadway and trapezoidal roadway; and when the ventilation air volume is increased, it is the three-centered arch. Through the gray correlation analysis, it can be seen that in order to improve the construction environment in the roadway after blasting, the rectangular section can be chosen when considering the air supply distance, and the three-centered arch can be chosen when considering the ventilation air volume.